2013
DOI: 10.1186/1744-9081-9-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between the GRM7 rs3792452 polymorphism and attention deficit hyperacitiveity disorder in a Korean sample

Abstract: BackgroundThe purpose of this study was to investigate the association between the ionotropic and glutamate receptors, N-methyl D-asparate 2A (GRIN2A) and 2B (GRIN2B), and the metabotropic glutamate receptor mGluR7 (GRM7) gene polymorphisms and attention-deficit hyperactivity disorder (ADHD) in Korean population.MethodsWe conducted a case–control analysis of 202 ADHD subjects and 159 controls, performed a transmission disequilibrium test (TDT) on 149 trios, and compared scores from the continuous performance t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 47 publications
(48 reference statements)
1
46
0
Order By: Relevance
“…In previous studies, GRM7 (mGluR7) has been shown to be associated with neurological disorders such as schizophrenia, hearing impairment and ADHD [48][49][50] . Although ELFN1 has not been reported as a major genetic factor for any neuropsychiatric disorder, we expect that further genetic investigation will demonstrate its involvement in neurodevelopmental disorders other than epilepsy and ADHD, given the shared genetic architecture among mental disorders that has been revealed in recent studies 51,52 .…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, GRM7 (mGluR7) has been shown to be associated with neurological disorders such as schizophrenia, hearing impairment and ADHD [48][49][50] . Although ELFN1 has not been reported as a major genetic factor for any neuropsychiatric disorder, we expect that further genetic investigation will demonstrate its involvement in neurodevelopmental disorders other than epilepsy and ADHD, given the shared genetic architecture among mental disorders that has been revealed in recent studies 51,52 .…”
Section: Discussionmentioning
confidence: 99%
“…GWAS have indicated that glutamatergic neurotransmission system genes were potentially associated with ADHD risk and/or symptoms, including GRIK1 (rs363512), GRIK4 (r s 655824) and GRM5 (rs5016282), and GRID2 (rs6815704) . Besides, GRIN2A , GRIN2B and GRM7 were also implicated in ADHD susceptibility and/or treatment . Magnetic resonance spectroscopy has shown that there was increased glutamatergic tone in the frontal and striatal brain regions of patients with ADHD .…”
Section: Introductionmentioning
confidence: 99%
“…8 Besides, GRIN2A, GRIN2B and GRM7 were also implicated in ADHD susceptibility and/or treatment. [9][10][11][12][13][14] Magnetic resonance spectroscopy has shown that there was increased glutamatergic tone in the frontal and striatal brain regions of patients with ADHD. [15][16][17] Additionally, glutamate uptake was discovered to be aberrant in the prefrontal cortex (PFC) of the spontaneous hypertensive rat (SHR, ADHD animal model).…”
mentioning
confidence: 99%
“…Although there has been work examining the effect of human glutamate metabotropic receptor 7 ( GRM7 ) polymorphisms on human substance use disorders, the majority of the work has focused on psychiatric disorders (Saus et al, 2010), including bipolar disorder (Alliey-Rodriguez et al, 2011), schizophrenia (Ganda et al, 2009; Ohtsuki et al, 2008; Shibata et al, 2009), major depressive disorder (Breen et al, 2011; Hamilton, 2011; Muglia et al, 2010; Pergadia et al, 2011; Shyn et al, 2011), panic disorder (Otowa et al, 2009), autism spectrum disorders (Yang & Pan, 2013), and ADHD (Elia et al, 2011; Park et al, 2013). Although not genome-wide significant, studies have found evidence for an association between GRM7 and nicotine dependence and cessation success (Uhl et al, 2010), and alcoholism (Li et al, 2011).…”
Section: Introductionmentioning
confidence: 99%